Exploring the efficacy of betulin in the development of novel local hemostatic agents: a scientific investigation - Kletnieks Karlis; Kletnieks Ugis; Sokolovsky, S.; Gladyshev, V.; Abramov, S.; Гладишев, Віталій Валентинович (My University, 2023)
This article aims to present a thorough and systematic analysis of the utilization of bioactive components obtained from diverse sources including minerals, synthetics, botanicals, and organics for the formulation of topical hemostatic agents. The study endeavors to assess the applicability of these agents, identify optimal combinations for clinical use, and scrutinize the underlying scientific principles governing their efficacy. Hemostasis, the biological process of arresting blood flow, constitutes a crucial aspect of surgical and medical interventions. Local hemostatic agents are widely deployed to achieve hemostasis in a targeted and controlled manner, thereby mitigating the potential hazards associated with bleeding. The use of biologically active constituents obtained